ELECTROCOAGULATION USING NOVEL CONFIGURATIONS ELECTRODES FOR TREATMENT OF TEXTILE WASTEWATER - Ahmed Samir Naje, 1981-, author; Zuriati Zakaria, Prof.DatinDr., supervisor; Shreeshivadasan Chelliapan, Dr., supervisor; Sekolah Razak UTM Dalam Kejuruteraan dan Teknologi Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016